The strategy of combining communism and technocracy and its impact on China's domestic and foreign policies (قضايا سياسية, 2025)
China is one of the countries that embrace communist ideology, and this ideology represents the main pillar of the state, which is represented by the ruling Communist Party of the country and clinging to power since the founding of the State of China until the present time. Despite the progress and successes achieved by communism for China and its global economic position, at the same time it has moved within a new strategy that combines communism and technocracy, by employing scientific expertise and competencies in managing the state, but in a new version "China's technocracy", which is pushing members of the Communist Party to develop their scientific level and manage state institutions, in addition to attracting scientific competencies and expertise outside the framework of the Communist Party and giving them a major role in managing the state. Although the concepts of technocracy indicate competencies and expertise far from any party or ethnic affiliations, China has proven through its experience of technocracy that it is not the monopoly of any ideology, but rather it is one of the pillars of the success of any state that aims to develop its political, economic and other entity.